2005
DOI: 10.1094/pd-89-0269
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the F129L Mutation in Alternaria solani on Fungicides Affecting Mitochondrial Respiration

Abstract: Isolates of Alternaria solani previously collected from throughout the Midwestern United States and characterized as being azoxystrobin sensitive or reduced sensitive were tested for sensitivity to the Quinone outside inhibitor (QoI) fungicides famoxadone and fenamidone and the carboxamide fungicide boscalid. All three fungicides affect mitochondrial respiration: famoxadone and fenamidone at complex III, and boscalid at complex II. A. solani isolates possessing reducedsensitivity to azoxystrobin also were less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
130
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(141 citation statements)
references
References 21 publications
7
130
1
3
Order By: Relevance
“…Target organisms can develop resistance to single-site antimicrobial compounds very rapidly, and in most cases resistance is traced back to a single genetic mutation in the target molecule that leads to a loss of recognition or metabolism of the antimicrobial compound. For example, A. solani has developed resistance to several commonly used fungicides, including azoxystrobin, due to single amino acid changes in the target molecules (8,11,(61)(62)(63). Resistance is often attributed to frequent use of antimicrobial compounds of the same class.…”
Section: Discussionmentioning
confidence: 99%
“…Target organisms can develop resistance to single-site antimicrobial compounds very rapidly, and in most cases resistance is traced back to a single genetic mutation in the target molecule that leads to a loss of recognition or metabolism of the antimicrobial compound. For example, A. solani has developed resistance to several commonly used fungicides, including azoxystrobin, due to single amino acid changes in the target molecules (8,11,(61)(62)(63). Resistance is often attributed to frequent use of antimicrobial compounds of the same class.…”
Section: Discussionmentioning
confidence: 99%
“…Estimating total annual crop losses due to any particular disease is difficult to do accurately. Values in the literature for crop losses due to early blight vary enormously from 5 to 78% (Waals et al 2004;Pasche et al 2004Pasche et al , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance has been reported in all major continents: Asia, Australia, Europe, North America, and South America (FRAC 2006;Wilson and Wicks, 2011). The majority of the reports associate the point mutation that results in a change from glutamate to alanine at codon 143 (G143A), followed by the resistance that results from a transition from phenylalanine to leucine at position 129 (F129L) (Pasche et al 2005;Sierotzki et al 2007); the least commonly observed mutation involves a change from glycine to arginine at position 137 (G137R) (Sierotzki et al 2007), and of course, unknown causes (Lesniak et al 2011). These easily identified mutations allow for the rapid detection for the potential of QoI-resistance in a variety of fungi and Chromista.…”
Section: Qoi-the Quinone Outside Inhibitorsmentioning
confidence: 99%